Penerapan konsep green sharia banking di Indonesia dalam mendukung Net Zero Emission 2060 - Rastinia Kamila Hanum; Deby Gita Anggraeni (Institute for Advanced Science Social, and Sustainable Future, 2023)
The summit in Glasgow is a big agenda for overcoming climate problems. As the owner of a large developing market in the world, Indonesia is also trying to reduce emissions produced by industry to achieve net zero emissions by 2060. Indonesia implements conventional and Sharia banking. Sharia banking is considered a means of achieving the goal of net zero emissions by 2060 because of environmentally friendly Sharia principles. The Green Sharia Banking concept is applied to solving the problems being researched. The research method is a literature review using various reading materials such as books and journals. Green Banking or Green Banking refers to financial investment for environmental programs in the context of balancing monetary chronological progress, stability of the natural environment, and protecting the ecology to achieve sustainable development. The concept of Green Sharia Banking and the goal of net zero emissions in 2060 in Indonesia are closely related because both initiatives have the same goal of reducing carbon emissions and promoting sustainable development. This concept is formulated in six pilot schemes to achieve net zero emissions by 2060. Collaboration with customers, suppliers, partners, and other stakeholders is needed so that Green Sharia Banking can create collective efforts to achieve carbon neutrality and promote sustainable development.